Zen and deep evolution: The optical delusion of separation. (23rd March 2018) - Allendorf, Fred W.
Abstract: The Buddha taught that everything is connected and constantly changing. These fundamental observations of the world are shared by ecology and evolution. We are living in a time of unprecedented rates of extinction. Science provides us with the information that we need to address this extinction crisis. However, the problems underlying extinction generally do not result from a lack of scientific understanding, but they rather result from an unwillingness to take the needed action. I present mindfulness and meditative aspects of Zen practice that provide the deeper "knowing, " or awareness that we need to inspire action on these problems.